2012
DOI: 10.1093/chromsci/bms001
|View full text |Cite
|
Sign up to set email alerts
|

Validated LC-MS-MS Method for the Determination of Quetiapine in Human Plasma: Application to a Pharmacokinetic Study

Abstract: A sensitive and selective liquid chromatography-tandem mass spectrometry (LC-MS-MS) method for the determination of quetiapine was developed and validated over the linearity range 1-1500 ng/mL with 0.1 mL of plasma using clozapine as the internal standard. Detection was performed on a triple-quadrupole tandem mass spectrometer using positive electrospray ionization and quantification was performed by selected reaction monitoring mode. The MS-MS ion transitions monitored were m/z 384.1 → 253.1 and 327.0 → 270.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…() reported 0.00618 and 0.018 µg ml −1 using ultra performance liquid chromatography‐ tandem mass spectrometry (UPLC‐MS/MS) and Pan et al . () and Davis et al . () found LLOQ of 0.001 and 0.0005 µg ml −1 respectively, both using LC–MS/MS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…() reported 0.00618 and 0.018 µg ml −1 using ultra performance liquid chromatography‐ tandem mass spectrometry (UPLC‐MS/MS) and Pan et al . () and Davis et al . () found LLOQ of 0.001 and 0.0005 µg ml −1 respectively, both using LC–MS/MS.…”
Section: Discussionmentioning
confidence: 98%
“…If we compare our analytical procedure with more sophisticated methodologies such as LC/tandem MS (LC-MS/MS), we find that they have lower LODs, as expected. Thus, Amundsen et al (2013) reported LOD and LLOQ of 0.00038 and 0.0038 μg ml À1 using an ultra high performance liquid chromatography-tandem mass spectrometry (UHPLC)-MS/MS, Proença et al (2013) reported 0.00618 and 0.018 μg ml À1 using ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) and Pan et al (2012) and Davis et al (2010) found LLOQ of 0.001 and 0.0005 μg ml À1 respectively, both using LC-MS/MS. Despite these differences, our limit of quantification is low enough to detect the lower therapeutic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, there are many ways to quantitatively analyze quetiapine in human biological samples such as HPLC,28 HPLC-MS/MS,29,30 and liquid chromatography (LC)/MS/MS 19,24,3133. However, method for BE study of 200 mg quetiapine XR in Chinese volunteers was only one; LC-MS/MS technology was used 34.…”
Section: Discussionmentioning
confidence: 99%
“…Various analytical methods have been reported in the literature to detect each medication separately with their metabolites and/or in combination with other medications in rat and human plasma as well as urine samples. These include gas chromatography (GC; da Fonseca et al ., ), capillary electrophoresis (CE; Deng et al ., ), thin‐layer chromatography (TLC; Soliman and Youssef, ), high‐performance liquid chromatography (HPLC; Belal et al ., ; Yeniceli and Dogrukol‐Ak, ; Suryakant and Sadhana, ), liquid chromatography–mass spectrometry (LC/MS; Zhou et al ., ; Raman et al ., ; Choong et al ., ), gas chromatography–mass spectrometry (GC/MS; Kakde et al ., ), liquid chromatography–tandem mass spectrometry (LC/MS/MS; Moreira et al ., ; Suresh et al ., ; Fisher et al ., ; Pan et al ., ; Parekh et al ., ) and ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC/MS/MS) (Li et al ., ; Tu et al ., ; Denooz et al ., ). However, no method has been reported to simultaneously determine BUP, ESC and QUE in plasma.…”
Section: Introductionmentioning
confidence: 99%